CLARIN The Infrastructure for Language Resources - Fišer, Darja; Witt, Andreas (Digital Linguistics, 2022)
The book provides a comprehensive overview of the Common Language Resources and Technology Infrastructure - CLARIN - for the humanities. It covers a broad range of CLARIN language resources and services, its underlying technological infrastructure, the achievements of national consortia, and challenges that CLARIN will tackle in the future. The book is published 10 years after establishing CLARIN as an Europ. Research Infrastructure Consortium.